Discrete Element Modeling of Full-Scale Ballasted Track Dynamic Responses from an Innovative High-Speed Rail Testing Facility. Issue 9 (September 2019) - Feng, Bin; Park, Eun Hyun; Huang, Haohang; Li, Wei; Tutumluer, Erol; Hashash, Youssef M.A.; Bian, Xuecheng
To achieve increased rail network safety and reliability, it is important to better understand ballast layer performance under complex and demanding dynamic loading field scenarios, especially for high speed lines on ballasted track. Repeated high-speed loading tests were recently conducted at three train speeds on a full-scale ballasted track-subgrade system, known as the Zhejiang University innovative high-speed rail tester (ZJU-iHSRT). BLOKS3D, a polyhedral discrete element method (DEM) particle simulation code with newly featured parallel computing capability, was used to capture the full-scale ballasted track dynamic responses at those speeds. A proportional–integral–derivative controller was also implemented in the DEM code to ensure identical dynamic loadings were applied in the DEM model as in the physical model. This paper presents the dynamic response findings obtained using the DEM model: 1) Crosstie vibration velocities captured in the DEM model match closely with the measurement obtained from the same crosstie in the physical model; 2) ballast particle vibration velocities recorded in the DEM model provide an overall good match with the data measured from the same location in the physical model; and finally, 3) visualized macroscopic ballast layer dynamic responses reveal the mechanical behavior of the ballast layer under dynamic loading scenarios applied in the ZJU-iHSRT full-scale ballasted track-subgrade system.